Design and modeling of inductors, capacitors and coplanar waveguides at tens of GHz frequencies - Pour Aryan, Naser (Springer International Publishing, 2015)
This book describes the basic principles of designing and modelling inductors, MIM capacitors and coplanar waveguides at frequencies of several tens of GHz. The author explains the design and modelling of key, passive elements, such as capacitors, inductors and transmission lines that enable high frequency MEMS operating at frequencies in the orders of tens of GHz.